EXPLORATORY STUDY ON IMPLEMENTATION OF ELECTRONIC HEALTH RECORDS (EHR) APPLICATIONS IN HOSPITALS OF KUWAIT DURING COVID 19 - Aya Mohamed (Journal of Informatics Education and Research, 2025)
The examination of this thesis focuses on how Electronic Health Records (EHR) systems were implemented in Kuwaiti hospitals during the COVID-19 pandemic and evaluates their effects on healthcare efficiency, outcomes and digital transformation. The study reveals Kuwait's healthcare system faces serious issues with EHR technology including interoperability gaps, cybersecurity threats, and inconsistent acceptance among stakeholders. Through the use of EHR systems this research examines how patient care can be improved while operations are streamlined along with modernizing healthcare delivery throughout Kuwait.